Global Phosphorus Fertilizer Market and National Policies: A Case Study Revisiting the 2008 Price Peak - Khabarov, Nikolay; Obersteiner, Michael (Frontiers in Nutrition, 2017)
The commodity market super-cycle and food price crisis have been associated with rampant food insecurity and the Arab spring. A multitude of factors were identified as culprits for excessive volatility on the commodity markets. However, as it regards fertilizers, a clear attribution of market drivers explaining the emergence of extreme price events is still missing. In this paper we provide a quantitative assessment of the price spike of the global phosphorus fertilizer market in 2008 focusing on diammonium phosphate (DAP). We find that fertilizer market policies in India, the largest global importer of phosphorus fertilizers and phosphate rock, turned out to be a major contributor to the global price spike. India doubled its import of P-fertilizer in 2008 at a time when prices doubled. The analysis of a wide set of factors pertinent to the 2008 price spike in phosphorus fertilizer market leads us to the discovery of a price spike magnification and triggering mechanisms. We find that the price spike was magnified on one hand by protective trade measures of fertilizer suppliers leading to a 19% drop in global phosphate fertilizer export. On the other hand, the Indian fertilizer subsidy scheme led to farmers not adjusting their demand for fertilizer. The triggering mechanism appeared to be the Indian production outage of P-fertilizer resulting in the additional import demand for DAP in size of about 20% of annual global supply. The main conclusion is that these three factors have jointly caused the spike, underscoring the need for ex-ante improvements in fertilizer market regulation on both national and international levels.